Salvage surgery for local recurrence after carbon ion radiotherapy for lung cancer: A case report. (2020) - Hara, Kantaro; Izumi, Nobuhiro; Tsukioka, Takuma; Komatsu, Hiroaki; Inoue, Hidetoshi; Miyamoto, Hikaru; Nishiyama, Noritoshi
Abstract: Background: The good local control rate of radiation therapy has been reported due to recent advances in irradiation technology. Carbon ion radiation therapy (CIRT) has been shown to be effective for early lung cancer. We report a case of performing salvage surgery on the local recurrence of lung cancer after CIRT. Case presentation: A 79-year-old man was referred to our hospital for treatment of local recurrence of left lung cancer at fifty nine months after CIRT. We performed wedge resection for diagnostic purposes. It was diagnosed as squamous cell carcinoma and was regarded as local recurrence. Subsequently, we performed left upper lobectomy and mediastinal lymph node dissection. The patient had recurrent lesions at 4 months after surgery and died 10 months after surgery. Conclusions: Surgery was safe even after CIRT. We considered that salvage surgery after CIRT may be one of the options of local control therapy for lung cancer.